The Spirituality of Love in the Bible: A Theological-Ethical Analysis in the Context of Globalization - Batubara, Sri Wahyuni; Arifinsyah, Arifinsyah (Prodi Studi Agama-Agama, 2026)
This study examines the spirituality of love in the Bible and its relevance to the challenges of globalization through a theological-ethical analysis. The article addresses three central concerns: how biblical teachings on love are understood as a foundation for spiritual and social life, how the values of love are expressed in contemporary Christian social practice, and what challenges globalization presents to the practice of those values. This study employs a qualitative design based on library research, drawing on biblical texts, theological works, and relevant scholarly literature on Christian ethics, spirituality, and globalization. The analysis shows that the spirituality of love in the Bible, especially as expressed through the concept of agape, functions as a theological and ethical framework that connects devotion to God with responsibility toward others. The study also finds that the values of love continue to shape Christian life in such areas as family, education, church ministry, and public engagement. At the same time, the practice of love faces significant pressures in the contemporary world, including materialism, individualism, consumerism, technological transformation, and secularization. In this context, the spirituality of love remains relevant as an ethical resource for sustaining compassion, solidarity, justice, and human dignity in an increasingly globalized society.